The Role of Equality and Equity in Social Preferences - Ernst Fehr; Michael Näf; Klaus M. Schmidt (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2005)
Engelmann and Strobel (AER 2004) question the relevance of inequity aversion in simple dictator game experiments claiming that a combination of a preference for efficiency and a Rawlsian motive for helping the least well-off is more important than inequity aversion. We show that these results are partly based on a strong subject pool effect. The participants of the E&S experiments were undergraduate students of economics and business administration who self-selected into their field of study (economics) and learned in the first semester that efficiency is desirable. We show that for non-economists the preference for efficiency is much less pronounced. We also find a non-negligible gender effect indicating that women are more egalitarian than men. However, perhaps surprisingly, the dominance of equality over efficiency is unrelated to political attitudes.
urn:nbn:de:bvb:19-epub-725-8
Keywords: C7; C91; C92; D63; D64; 330; Social Preferences; Inequity Aversion; Efficiency Preferences